Kraus' recreation and leisure in modern society - Hurd, Amy R.; Anderson, Denise M. 1970-; Mainieri, Tracy
"Kraus' Recreation and Leisure in Modern Society provides a detailed introduction to the history, developments, and current trends in leisure studies"--Provided by publisher.
Conceptual foundations of the field of leisure services -- Leisure motivation -- Sociocultural factors affecting leisure experiences -- History of recreation and leisure -- Social functions of community recreation -- The leisure-service system -- Leisure as a profession -- Specialized leisure service areas -- Outdoor recreation and natural resources management -- Travel and tourism -- Sport and the leisure industry -- Future perspectives.
CAC Camia (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Recreation -- North America -- History; Leisure -- Social aspects -- North America; Play -- North America -- Psychological aspects; Recreation -- Vocational guidance -- North America